PENGUATAN BRANDING JAJE GINA DI BATUBULAN GIANYAR MELALUI SOSIAL MEDIA MARKETING DAN SISTEM ADMINISTRASI SEDERHANA - I Putu Widyarsana; Putu Eny Suhardiyani; I Gusti Putu Hardi Yudana (Jurusan Informatika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Udayana, 2026)
MSMEs (Micro, Small, and Medium Enterprises) that produce traditional snacks like Jaje Gina play a strategic role in fulfilling religious ritual needs. The name